A CONSTITUIÇÃO DA DOCÊNCIA DE PROFESSORES DE HISTÓRIA DA ARTE DO CURSO DE LICENCIATURA EM ARTES VISUAIS – EAD – UAB/UFES: DIÁLOGOS ENTRE A MODALIDADE A DISTÂNCIA E A PRESENCIAL - Almonfrey, Juliana de Souza Silva (2020)
The present study focuses on the performance of Art History professors who became part of the teaching staff of the undergraduate course in Visual Arts in Distance Education (DE) at the Federal University of Espírito Santo. The questions that problematize